2017
DOI: 10.1166/jnn.2017.12403
|View full text |Cite
|
Sign up to set email alerts
|

Supramolecular Hydrogels Based on MPEG-Grafted Hyaluronic Acid and α-CD Containing HP-β-CD/Simvastatin Enhance Osteogenesis In Vivo

Abstract: Simvastatin (SIM) accelerates new bone formation both in vitro and In Vivo by enhancing the expression of recombinant human bone morphogenetic protein-2 (rhBMP-2). In this study, we evaluated the effect of water-solubility of SIM on new bone formation by preparing two types of supramolecular hydrogels: pseudopolyrotaxanes (PPRXs) based on metoxy polyethyleneglycol-grafted hyaluronic acid (MPEG-g-HA) and α-cyclodextrin (α-CD) containing water-soluble hydroxypropyl β-cyclodextrin/simvastatin inclusion complex (H… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2021
2021
2022
2022

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(4 citation statements)
references
References 0 publications
0
4
0
Order By: Relevance
“…Longitudinal sections of whole tail were cut at 6 μm using a cryostat followed by Goldner's trichrome staining protocol as previously described. 25 Briefly, the slides were mordanted in Bouin's Fluid solution and stained with Weigert's hematoxylin, ponceau acid fuchsin and then costained with light green respectively. Five to six mice were evaluated in each group.…”
Section: Methodsmentioning
confidence: 99%
“…Longitudinal sections of whole tail were cut at 6 μm using a cryostat followed by Goldner's trichrome staining protocol as previously described. 25 Briefly, the slides were mordanted in Bouin's Fluid solution and stained with Weigert's hematoxylin, ponceau acid fuchsin and then costained with light green respectively. Five to six mice were evaluated in each group.…”
Section: Methodsmentioning
confidence: 99%
“…Hydrogel materials are also excellent carriers for simvastatin because of their three-dimensional network structure, flexibility, and moisture content. ,, These properties give them the ability to embed bone-forming drugs such as simvastatin into their network structures. Hydrophilic hydrogel materials induce weaker local inflammatory responses than their hydrophobic counterparts because fewer protein components adsorb onto their surfaces.…”
Section: Simvastatin-loaded Drug Delivery Systemsmentioning
confidence: 99%
“…In addition, increasing the systemically administered dose increases the risk of side effects such as liver damage, kidney disease, and rhabdomyolysis. Therefore, several drug delivery system studies have been performed with the goal of directly delivering simvastatin to bone defect sites. These studies have demonstrated the ability to induce bone repair. , …”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation